A comparative review of dental materials used in the biological method of treatment of chronic forms of pulpitis in the teeth of raw roots (LLC "Endo Press", 2020)
Review of the literature on the role of the dental pulp, of her high reserve opportunities of the regeneration plan shows that the inflammatory character in the pulp of the tooth is the reversible process. The use of medicinal drugs is possible preservation of the viability of the pulp. This requires treatment of the materials covering inflammation of the pulp. The conservative method of treatment of pulpitis provides for the application of therapeutic liners, restoring the structural and functional properties of the pulp. In this paper, we present the review of preparations used in the biological method of treatment of pulpitis according to the russian and international literature.